(untitled) (Conversatoria Linguistica, 2019)
This article lists and briefly describe sage related changes in the stomatognathic system. And that established understanding, may become a serious support to the work of elderly people’s therapists. The changed to the stomatognathic system affect both general health condition, chewing, swallowing, speaking abilities, as well as wellbeing and self esteem of seniors. Moreover, at present, the knowledge on stomatognathic in elderly is fairly underestimated by doctors and other experts. The significant lack of developed logopaedic thesis on this aspect also brings in more unawareness.